Chapter 5 anni di monitoraggio, controllo e prevenzione della pesca illegale nel Parco Sommerso di Gaiola (Golfo di Napoli) - Simeone, Maurizio (Proceedings e report, 2020)
The Gaiola Underwater Park is a small Marine Protected Area located in Naples (Italy), funded in 2002 to preserve the biological and archaeological heritage. In fact, because of the metropolitan context in which it is integrated, the area is subject to constant anthropic pressure, which often results in illegal activities, especially in the fishing sector. In this work, the results of 5 years of monitoring and control of illegal fishing inside the MPA are presented. This research had an important impulse in 2015, thanks to the collected data and to the methodology developed within the Gaiola MedPAN Project. The experience acquired in these years resulted in the funding of the StAMM Project, a permanent station for the monitoring, control and prevention of environmental offences in the MPA.